2015
DOI: 10.1108/jbim-07-2013-0152
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge transfer between actors in the innovation system: a study of higher education institutions (HEIS) and SMES

Abstract: Purpose – The purpose of this paper is to understand how and why small to medium enterprises (SMEs) access knowledge from external actors in general and from higher education institutions (HEIs) in particular and what is the extent to which these knowledge access pathways affect SME innovativeness. Design/methodology/approach – The paper involved both quantitative and qualitative approaches: a survey of 1,226 SMEs and a mini case study t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 103 publications
(156 reference statements)
1
38
0
1
Order By: Relevance
“…This study investigates the practical issues associated with KM in consultancy-involved process improvement projects in SMEs. As acknowledged by Chen et al (2006), de Zubielqui et al (2015 and Pillania (2008), SMEs often need to seek external learning sources due to their resource constraints. In this study, SME owners employed consultants to help them learn new knowledge of process improvement practices.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study investigates the practical issues associated with KM in consultancy-involved process improvement projects in SMEs. As acknowledged by Chen et al (2006), de Zubielqui et al (2015 and Pillania (2008), SMEs often need to seek external learning sources due to their resource constraints. In this study, SME owners employed consultants to help them learn new knowledge of process improvement practices.…”
Section: Discussionmentioning
confidence: 99%
“…The relatively low level of specialisation in SMEs means they may lack adequate expertise to conduct KM activities (Wong and Aspinwall 2004). It is therefore important for SMEs to use external knowledge sources such as business partners and management consultants to facilitate their KM processes (Chen et al 2006;Chirico 2008;de Zubielqui et al 2015;Liao and Barnes 2015;Pillania 2008;Zhang et al 2006). For this study, we focus on the practical KM issues encountered by SMEs when involved in consultancy projects.…”
Section: Knowledge Management In Smesmentioning
confidence: 99%
“…We examined the references of the remaining 84 articles to check for relevant works frequently cited but not yet added in our review. The quantitative analysis of references did not result in the inclusion of any study, and the literature portfolio used in the study comprised these 84 studies (Abbott, 2019;Athukorala et al, 2017;Baird et al, 2011;Barnes, 2017;Beaumont, 2005;Beer, 2018;Black et al, 2015;Boaden & Sims, 2000;Boer et al, 2005;Caldera et al, 2018;Cantù et al, 2015;Clibborn, 2012;Cooney;Correia et al, 2020;Craik, 2015;Cripps et al, 2009;Dargusch & Ward, 2010;Feng et al, 2008;Fraser et al, 2013;Given, 2017;Grodach & Martin, 2020;Hasan et al, 2011;Hu et al, 2019;Jackson et al, 2018;Jayaram et al, 2014;Joiner et al, 2009;Jones, 2005;Karim et al, 2008;Kiridena et al, 2009;Le & Valadkhani, 2014;Leahy et al, 2010;Lo & Power, 2010;Lobo et al, 2009Lobo et al, , 2012Lobo et al, , 2018Logue et al, 2015;Low et al, 2007;Marks, 2009;Mo, 2009;MoosaviRad et al, 2014;Nelson et al, 2007;…”
Section: Methodsmentioning
confidence: 99%
“…The comparative analysis between the contribution to the regional economic development made by universities in the United States and the European Union, based on empirical studies, is the subject of analysis by several authors, who have concluded that the common aspects that promote KT are: the proximity of the universities to businesses and the skills of the professors and within the academic discipline, in which the regional colleges have a significant influence, given their economic conditions, recognizing that regional economic development is perceived as a social responsibility of the educational institutions in the globalized knowledge economy (Goldstein et al, 2013;Urbano & Guerrero, 2013;Guerrero et al, 2014;Corral et al, 2015;Bellucci & Pennacchio, 2016;Guerrero et al, 2016).…”
Section: Discussion Of the Topic: The Economic Impact Of The Universimentioning
confidence: 99%